Structure transformation in amorphous Fe-B ribbon under laser scanning - Nykyruy, Yulia; Sembratovych, Nazar (Physics and Chemistry of Solid State, 2024)
Amorphous Fe86B14 alloy produced by the melt quenching technique was processed by pulsed fibber laser in scanning mode with various scanning speed and laser power. X-ray diffraction method was used to study the laser-induced structure evolution in the amorphous ribbon. Nanosized grains of α-Fe phase were observed as a result of partial crystallization.